LATAR, TEMA, AMANAT, DAN KRITIK SOSIAL DALAM NOVEL â€œ86â€ KARYA OKKY MADASARI - FX. Suwardo, FX. Suwardo (Widya Warta, 2014)
The research aimed to find and describe the intrinsic structure of the novel â€œ86â€ written by Okky Madasari. It includes setting, theme, message, and social criticism. Hence, the researchdesign applied was qualitative descriptive method. The data of the research were all texts which contain sentences, paragraphs, and discourses related to the main problem of analysis.Automatically, the researcher became the main instrument of the research. The results of the research were (1) the spatial setting of the novel was Jakarta, Solo, Ponorogo, and Klaten; thetemporal setting of the novel was the work days, morning, afternoon, and evening; the social setting of the novel was the educated middle-upper class society, (2) the main theme of thenovel was not far different from the traditional theme in which someone who commits power abuse by conducting corruption, for instance, will be arrested and get punishment; while, theadditional theme was (a) the pride of parents who could support their children to get higher education and good job, (b) the frequent practice of misusing the authority, such as the case ofcorruption in the law enforcement, (c) the assumption and opinion that money plays great role, (3) the moral message from the author of the novel was to declare that (a) the powerabuse, such as trading court case in the law enforcement is getting worse, (b) the work atmosphere and the leadership of the chief give much influence to the performance of the staff,(c) the situation of the prison which should be the place for the prisoner rehabilitation was ironic, and (4) the social criticism in the novel was (a) the traffic jam in Jakarta, (b) thenepotism in the recruitment of civil servant, (c) the unprofessional performance of law enforcement. Based on the findings of the research, the researcher suggests that the novel â€œ86â€Â  should be proposed to be the reference in the subject of literary criticism and comprehension in high school and higher education. Besides, the novel â€œ86â€ should be distributed to libraries including school library, government library, as well as national and regional public services.